Previous antibiotic use and the development of Kawasaki disease: a matched pair case‐control study. Issue 9 (14th September 2020) - Fukazawa, Mitsuharu; Fukazawa, Mitsuru; Nanishi, Etsuro; Nishio, Hisanori; Ichihara, Kiyoshi; Ohga, Shouichi
Abstract: Background: Kawasaki disease (KD) is an acute febrile illness with systemic vasculitides, mostly affecting infants and young children. The etiology of KD is still unclear; however, altered gut microbiota have been recently implicated as a contributing factor for the development of vasculitis. Methods: We conducted an age‐ and gender‐matched case‐control study on 50 patients and 200 control subjects to search for potential factors leading to intestinal dysbiosis associated with KD. Data were analyzed using conditional multivariable logistic regression. Results: Previous antibiotic administration was associated with the patients who developed KD (odds ratio [OR] 11.7, 95% confidence interval [CI] 4.7−29.1, P < 0.0001), but not other variables, including breastfeeding and group nursery. In subgroup analyses, cesarean birth was indicated as an associated factor in addition to previous antibiotic administration in infants under 12 months of age (OR: 8.0, 95% CI: 1.8−34.4, P = 0.005), but not in older children. Conclusions: The association between previous antibiotic administration and the onset of KD was demonstrated. Antibiotics may contribute to the development of KD by affecting the intestinal microbiota in infants and young children.